The synergy of political stability, trade liberalization, and macroeconomic factors in attracting FDI to Pakistan - Haidari, Adila; Junejo, Safiullah; Wicaksono, Teguh Yudo (Universitas Muhammadiyah Yogyakarta, 2026)
The determinants of foreign direct investment (FDI) in Pakistan remain a subject of ongoing debate, particularly regarding the relative influence of political stability compared to economic factors. This study investigates the interplay between political stability, trade liberalization, and macroeconomic factors in shaping FDI inflows in Pakistan from 1990 to 2023. Employing a quantitative approach using multiple linear regression on time-series data, this study evaluates the impact of political stability, trade liberalization, exports, imports, and inflation on FDI. The empirical findings indicate that political stability does not exert a statistically significant influence on foreign direct investment (FDI) in Pakistan, whereas export growth, trade liberalization, and price stability emerge as key determinants. A 1% increase in exports is associated with a 0.78% increase in FDI, underscoring the importance of economic fundamentals relative to political considerations. These results suggest that economic fundamentals may play a more decisive role in shaping FDI dynamics in the context of Pakistan. From a policy perspective, the findings underscore the importance of strengthening trade openness, promoting export diversification, and maintaining macroeconomic stability to improve the country’s investment environment. By examining the combined effects of several relatively underexplored determinants of FDI in Pakistan, this study contributes to the literature by providing additional empirical evidence on the drivers of foreign investment in developing economies facing similar structural and macroeconomic challenges.